2022
DOI: 10.1038/s41437-022-00518-0
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic differentiation and genomic signatures of adaptation to climate in an abundant lizard

Abstract: Species distributed across climatic gradients will typically experience spatial variation in selection, but gene flow can prevent such selection from causing population genetic differentiation and local adaptation. Here, we studied genomic variation of 415 individuals across 34 populations of the common wall lizard (Podarcis muralis) in central Italy. This species is highly abundant throughout this region and populations belong to a single genetic lineage, yet there is extensive phenotypic variation across cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…For example, the long‐term geographic isolation and climatic heterogeneity in southwestern China might have shaped genetic diversification and promoted local adaptation of the evergreen oak Quercus kerrii (Jiang et al, 2018). Similarly, a previous study revealed that climatic variability had played a major role in shaping population genetic differentiation of the lizard Podarcis muralis in central Italy (Minano et al, 2022). In this study, we found distinct climate differences between habitats of European and Chinese D. galeata populations based on 19 climate variables: European populations inhabited a “cold and dry” climate whereas Chinese populations inhabited a “hot and wet” climate.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…For example, the long‐term geographic isolation and climatic heterogeneity in southwestern China might have shaped genetic diversification and promoted local adaptation of the evergreen oak Quercus kerrii (Jiang et al, 2018). Similarly, a previous study revealed that climatic variability had played a major role in shaping population genetic differentiation of the lizard Podarcis muralis in central Italy (Minano et al, 2022). In this study, we found distinct climate differences between habitats of European and Chinese D. galeata populations based on 19 climate variables: European populations inhabited a “cold and dry” climate whereas Chinese populations inhabited a “hot and wet” climate.…”
Section: Discussionmentioning
confidence: 71%
“…For example, the long-term geographic isolation and climatic heterogeneity in southwestern China might have shaped genetic diversification and promoted local adaptation of the evergreen oak Quercus kerrii (Jiang et al, 2018). Similarly, a previous study revealed that climatic variability had played a major role in shaping population genetic differentiation of the lizard Podarcis muralis in central Italy (Minano et al, 2022) We identified 4568 SNPs in D. galeata that were significantly associated with climatic PC1, which mainly reflects variation in annual mean temperature. Some genes linked to these SNPs have been previously implicated in climate adaptation, such as the ecdysone signalling gene dib and sad (Ma, Li, et al, 2019) and the stress response gene HSP90B1 (Sandoval-Castillo et al, 2020).…”
Section: Morphological Variabilitymentioning
confidence: 68%
“…However, our results did not reveal isolated lines, but almost null or very shallow divergence amongst P. muralis populations within the mtDNA clades in this area. Yet, the use of nuclear markers ( Psonis et al 2018 , Yang et al 2020 , Yang et al 2022 , Ruiz-Miñano et al 2022 ) is needed for assessing more detailed patterns of variation.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we study population divergence in maternal investment, and embryo energy use and allocation across a climatic gradient in the widespread common wall lizard Podarcis muralis (Figure 1a) from the western Italian coast eastward into the Apennine mountains in central Italy. Wall lizards are abundant across this region, which spans >800 m in altitude and represent a transition in climatic regime from warm (low altitude) to cool (high altitude) climate (Ruiz Miñano et al, 2022). There is likely no single mechanism acting to compensate for the greater energy cost associated with embryonic development in cool climates, but rather a suite of complementary mechanisms.…”
Section: Introductionmentioning
confidence: 99%